ANALISIS MODEL CONTEXTUAL TEACHING LEARNING (CTL) BERBANTU MEDIA MINIATUR PADA PEMBELAJARAN SAINS KELAS III SD (JS (JURNAL SEKOLAH), 2021)
Abstract: The purpose of this study is to describe the learning planning of the Contextual Teaching Learning (CTL) model. Describing student responses during the learning process using the Contextual Teaching Learning (CTL) model. Analyzing the constraints found in learning using the Contextual Teaching Learning (CTL) model. The type of data used in this study is qualitative data, which is expressed in the form of sentences or descriptions. In order to obtain this qualitative data, the researchers conducted an understanding of the meaning of the Contextual Teaching Learning (CTL) model analysis assisted by miniature media in science learning which focused on analyzing the use of Contextual Teaching Learning models during learning. The result of this research is that learning planning in grade 3 of SDN Sogaten, Madiun City is carried out starting from choosing a theme, making semester programs, making lesson plans, and planning assessments. Student response to the Contextual Teaching and Learning learning model is very good. It is evident that the average or percentage of the results of the questionnaire shows that more than 94% respond well to this learning model. Constraints include: 1) between the subject matter and the real world is sometimes difficult to combine, and 2) the limited number of hours so that it is difficult to bring students to directly spacious.Keyword: Contextual Teaching Learning (CTL), Miniature Environment, Science LearningAbstrak: Tujuan penelitian ini adalah untuk mendeskripsikan perencanaan pembelajaran model Contextual Teaching Learning (CTL). Mendeskripsikan respon siswa selama proses pembelajaran menggunakan model Contextual Teaching Learning (CTL). Menganalisis kendala-kendala yang ditemukan dalam pembelajaran menggunakan model Contextual Teaching Learning (CTL). Jenis data yang digunakan dalam penelitian ini adalah data kualitatif, yang dinyatakan dalam bentuk kalimat atau uraian. Dalam rangka mendapatkan data kualitatif ini, maka peneliti melakukan pemahaman makna tentang analisis model Contextual Teaching Learning (CTL) berbantu media miniatur dalam pembelajaran sains yang difokuskan pada analisis penggunaan model Contextual Teaching Learning selama pembelajaran. Hasil dari penelitian ini adalah Perencanaan pembelajaran pada kelas 3 SDN Sogaten Kota Madiun dilakukan mulai dari pemilihan tema, pembuatan program semester, pembuatan RPP, dan rencana penilaian. Respon siswa terhadap model pembelajaran Contextual Teaching and Learning sangat baik. Ini terbukti bahwa rata rata atau persentase hasil angket menunjukan lebih dari 94% menanggapi model pembelajaran ini dengan baik. Kendala-kendala antara lain: 1) antara materi pelajaran dengan dunia nyata terkadang sulit dipadukan, dan 2) jumlah jam pelajaran yang terbatas sehingga kesulitan membawa siswa untuk langsung kelapangan.Kata Kunci : Contextual Teaching Learning (CTL), Miniatur Linkungan, Pembelajaran Sains